Prediction of Non-canonical Routes for SARS-CoV-2 Infection in Human Placenta Cells - Flávia Bessi Constantino; Sarah Santiloni Cury; Célia Regina Nogueira; Robson Francisco Carvalho; Luís Antônio Justulin (2021)
The SARS-CoV-2 is the causative agent of the COVID-19 pandemic. The data available about COVID-19 during pregnancy have demonstrated placental infection; however, the mechanisms associated with intrauterine transmission of SARS-CoV-2 is still debated. Intriguingly, while canonical SARS-CoV-2 cell entry mediators are expressed at low levels in placental cells, the receptors for viruses that cause congenital infections such as the cytomegalovirus and Zika virus are highly expressed in these cells. Here we analyzed the transcriptional profile (microarray and single-cell RNA-Seq) of proteins potentially interacting with coronaviruses to identify non- canonical mediators of SARS-CoV-2 infection and replication in the placenta. Despite low levels of the canonical cell entry mediators ACE2 and TMPRSS2, we show that cells of the syncytiotrophoblast, villous cytotrophoblast, and extravillous trophoblast co-express high levels of the potential non-canonical cell-entry mediators DPP4 and CTSL. We also found changes in the expression of DAAM1 and PAICS genes during pregnancy, which are translated into proteins also predicted to interact with coronaviruses proteins. These results provide new insight into the interaction between SARS-CoV-2 and host proteins that may act as non-canonical routes for SARS-CoV-2 infection and replication in the placenta cells.